A critical analysis of the 8th edition TNM staging for head and neck cutaneous squamous cell carcinoma with lymph node metastases and comparison to N1S3 stage and ITEM risk score: A multicenter study. Issue 7 (15th March 2021) - Ebrahimi, Ardalan; Luk, Peter P.; Low, Hubert; McDowell, Lachlan; Magarey, Matthew J. R.; Smith, Paul N.; Perriman, Diana M.; Veness, Michael; Gupta, Ruta; Clark, Jonathan R.
Abstract: Background and Objectives: We performed a critical analysis of the 8th edition American Joint Committee on Cancer (AJCC) staging for head and neck cutaneous squamous cell carcinoma (HNcSCC) with nodal metastases and compared the performance to the N1S3 and ITEM systems. Methods: Multicenter study of 990 patients with metastatic HNcSCC treated with curative intent. The end points of interest were disease‐specific (DSS) and overall survival (OS). Model fit was evaluated using Harrell's Concordance Index (C‐index), proportion of variation explained (PVE), Akaike information criterion, and Bayesian information criterion. Results: N1S3 and ITEM demonstrated good distribution into risk categories in contrast to the AJCC system, which classified the majority (90.6%) of patients as N2‐3 and Stage IV due to the high rate of extranodal extension. The N2c and N3a categories appeared redundant. There was considerable discordance between systems in risk allocation on an individual patient basis. N1S3 was the best performed (DSS: C‐index 0.62, PVE 10.9%; OS: C‐index 0.59, PVE 4.5%), albeit with relatively poor predictive value. Conclusions: The AJCC N category and tumor node metastasis stage have poor patient distribution and predictive performance in HNcSCC. The AJCC stage, N1S3, and ITEM score all provide limited prognostic information based on objective measures highlighting the need to develop a staging system specific to HNcSCC.